ANALISIS PENENTUAN POLA DATA PENDUDUK BERHAK MENDAPAT BANTUAN MENGGUNAKAN ALGORITMA APRIORI - Siti Aliyah; Efani Desi; M. Irfan Aldy Nasution (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Data collection is a process of proving a research result which is used as the basis for studies and opinions. The problem of poverty has always been a fundamental problem that continues to be faced by society. With the problems that exist, the researcher uses a set of data by analyzing a number of population data in the database using data mining with the a apriori algorithm method to produce information. The a apriori algorithm calculation performed by the author retrieved 150 population data to be processed. the results of the research and discussion that have been carried out by researchers that the analysis process of determining population data patterns is entitled to assistance using the a apriori algorithm method can be seen based on a combination of 2 itemsets with a tendency value on unstable income and cement floors in houses with a minimum support value of 70% and minimum value of 84% confidence.